(untitled) (Perner’s Contacts, 2018)
The article is focused on the issue of the activity at the dispatching workplace of a smaller transport company dealing with road transport by own trucks up to 3.5 tons. It describes and analyze the basic activities of the dispatcher and select the problems of the dispatching activities. To understand the risks, SWOT analysis is included. The article also points to risks arising from the activity of the driver.